Adaptive fuzzy wavelet network control of second order multi-agent systems with unknown nonlinear dynamics. (July 2017) - Taheri, Mehdi; Sheikholeslam, Farid; Najafi, Majddedin; Zekri, Maryam
Abstract: In this paper, consensus problem is considered for second order multi-agent systems with unknown nonlinear dynamics under undirected graphs. A novel distributed control strategy is suggested for leaderless systems based on adaptive fuzzy wavelet networks. Adaptive fuzzy wavelet networks are employed to compensate for the effect of unknown nonlinear dynamics. Moreover, the proposed method is developed for leader following systems and leader following systems with state time delays. Lyapunov functions are applied to prove uniformly ultimately bounded stability of closed loop systems and to obtain adaptive laws. Three simulation examples are presented to illustrate the effectiveness of the proposed control algorithms. Highlights: Use of adaptive fuzzy wavelet networks in multi-agent systems. Reach to consensus in leaderless and leader following nonlinear multi-agent systems Addressing consensus tracking problem of multi-agent systems with state time delays.